Chronic kidney disease in the elderly: evaluation and management. (September 2014) - Mallappallil, Mary; Friedman, Eli A; Delano, Barbara G; McFarlane, Samy I; Salifu, Moro O
Chronic kidney disease (CKD) is a very common clinical problem in elderly patients and is associated with increased morbidity and mortality. As life expectancy continues to improve worldwide, there is a rising prevalence of comorbidities and risk factors such as hypertension and diabetes predisposing to a high burden of CKD in this population. The body of knowledge on the approach to elderly patient with CKD is still evolving. Thus, this review seeks to explore the epidemiology and to discuss current understanding of challenges in the diagnosis and management of elderly patients CKD.